Efficacy of Tai Chi-Style Multi-Component Exercise on Frontal-Related Cognition and Physical Health in Elderly With Amnestic Mild Cognitive Impairment - Yang, Shao-Yun; Lee, Hsuei-Chen; Huang, Chih-Mao; Chen, Jin-Jong (Frontiers in Aging, 2021)
The present study examined the effects of the multi-component exercise training (Tai-Chi exercise, Aerobic fitness, and thera band) on neurocognitive function and functional fitness in older participants with amnestic mild cognitive impairment (aMCI). Participants with aMCI (n = 36) in the quasi-experimental design were assigned to the multi-component exercise group or care control group. Evaluations of neuropsychological function and functional fitness were performed before and after 12-week intervention, and after 24-week follow-up. Our results showed that the multi-component intervention significantly improved various domains of neurocognitive function, particularly in memory- and frontal-related cognition, and better performance on functional fitness, including muscle strength, cardiopulmonary endurance, and agility. Such beneficial effects were preserved after 24 weeks. The findings provide supportive evidence that multi-component exercise may protect against age-related neurocognitive and physical deficits and lay the path on developing age-friendly intervention programs to promote mental and physical health among the elderly populations.